The effects of aerobic exercise training on oxidant-antioxidant balance, neurotrophic factor levels, and blood-brain barrier function in obese and non-obese men - Hee-Tae Roh; Wi-Young So (Elsevier, 2017)
Purpose: The purpose of this study was to investigate the effects of obesity and aerobic exercise training on oxidant-antioxidant balance, neurotrophic factor levels, and blood-brain barrier (BBB) function. Methods: Ten non-obese healthy men (body mass index < 25 kg/m2) and 10 obese men (body mass index ≥ 25 kg/m2) were included in the study. Both groups performed treadmill exercise for 40 min 3 times weekly for 8 weeks at 70% heart rate reserve. Blood samples were collected to examine oxidant-antioxidant balance (reactive oxygen species (ROS) and superoxide dismutase (SOD) activity levels), neurotrophic factors (brain-derived neurotrophic factor (BDNF), nerve growth factor, and glial cell line-derived neurotrophic factor levels), and BBB function (S100β and neuron-specific enolase (NSE) levels) before and after exercise training. Results: The obese group showed significantly greater changes than the non-obese group in serum ROS (−0.46 ± 0.31 mmol/L vs. −0.10 ± 0.17 mmol/L, p = 0.005), serum S100β levels (−8.50 ± 5.92 ng/L vs. −0.78 ± 5.45 ng/L, p = 0.007), and serum NSE levels (−0.89 ± 0.54 µg/L vs. −0.01 ± 0.74 µg/L, p = 0.007) after training. At baseline, the obese group showed significantly higher serum ROS and S100β levels and significantly lower serum SOD activity and BDNF levels than the non-obese group (p < 0.05). The obese group showed significantly lower serum ROS, S100β, and NSE levels and significantly higher serum SOD activity and BDNF levels after training compared with baseline (p < 0.05). Conclusion: These results suggest that obesity can reduce serum neurotrophic factor levels and can induce BBB dysfunction. On the other hand, aerobic exercise can improve an oxidant-antioxidant imbalance in obese subjects and limit BBB dysfunction.